PERAN GURU PAI DALAM MENGINTERNALISASIKAN NILAI-NILAI PENDIDIKAN ISLAM BAGI KEMANDIRIAN SISWA DI SEKOLAH LUAR BIASA SINAR HARAPAN 2 - Rohmatin Ramadhani; Devy Habibi Muhammad; Maulid Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Independence is an essential competency that should be developed among students with special needs through educational practices tailored to their characteristics. In this context, Islamic Religious Education (IRE) teachers play a strategic role in internalizing Islamic educational values as the foundation for developing students' independence. This study aims to analyze the Islamic educational values internalized, the roles, strategies, and methods employed by IRE teachers, as well as the outcomes of the internalization process in fostering students' independence at Sinar Harapan 2 Special School. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the Islamic educational values internalized include responsibility, discipline, self-confidence, perseverance, patience, trustworthiness, cleanliness, and neatness. The internalization process was implemented through exemplary behavior (uswah hasanah), habituation, demonstration, learning by doing, individualized assistance, and positive reinforcement supported by collaboration between teachers and parents. These efforts contributed positively to students' independence in personal, social, and spiritual dimensions, as reflected in improved responsibility, discipline, self-care skills, self-confidence, social awareness, and religious character. The findings indicate that the successful development of independence among students with special needs is influenced not only by the delivery of Islamic Religious Education content but also by the effective internalization of Islamic values through consistent role modeling, habituation, direct experience, and collaboration between schools and families.